Epstein-Barr Virus- (EBV-) Immortalized Lymphoblastoid Cell Lines (LCLs) Express High Level of CD23 but Low CD27 to Support Their Growth - Hooi-Yeen Yap; Thin-Sam Siow; Sook-Khuan Chow; Sin-Yeang Teow (Advances in Virology)
Epstein-Barr virus (EBV) is one of the common human herpesvirus types in the world. EBV is known to infect more than 95% of adults in the world. The virus mainly infects B lymphocytes and could immortalize and transform the cells into EBV-bearing lymphoblastoid cell lines (LCLs). Limited studies have been focused on characterizing the surface marker expression of the immortalized LCLs. This study demonstrates the generation of 15 LCLs from sixteen rheumatoid arthritis (RA) patients and a healthy volunteer using B95-8 marmoset-derived EBV. The success rate of LCL generation was 88.23%. All CD19+ LCLs expressed CD23 (16.94-58.9%) and CD27 (15.74-80.89%) on cell surface. Our data demonstrated two distinct categories of LCLs (fast- and slow-growing) (p<0.05) based on their doubling time. The slow-growing LCLs showed lower CD23 level (35.28%) compared to fast-growing LCLs (42.39%). In contrast, the slow-growing LCLs showed higher percentage in both CD27 alone and CD23+CD27+ in combination. Overall, these findings may suggest the correlations of cellular CD23 and CD27 expression with the proliferation rate of the generated LCLs. Increase expression of CD23 may play a role in EBV immortalization of B-cells and the growth and maintenance of the EBV-transformed LCLs while CD27 expression might have inhibitory effects on LCL proliferation. Further investigations are warranted to these speculations.